SARA’S REPRESENTATION IN DETIK.COM NEWS PORTAL (Norman Fairclough's Critical Discourse Analysis Statement by the Head of BPIP Calling Religion to be the Greatest Enemy of Pancasila) - Andhika Prayoga; Mayasari Mayasari; Fardiah Oktariani Lubis (Universitas Bunda Mulia, 2020)
Sara's Representation in Detik.com News Portal (Norman Fairclough's Critical Discourse Analysis Statement by the Head of BPIP Calling Religion to be the Greatest Enemy of Pancasila). This research was compiled because of the interest of researchers to see how SARA is represented in the statement of the Head of BPIP who said religion was the greatest enemy of Pancasila in detik.com. This study uses qualitative research methods using the theory of critical discourse analysis. Critical Discourse Analysis used is the Norman Fairclough AWK model that emphasizes the three dimensions of Fairclough namely text, discourse practice and sociocultural practice that focuses on the content of the text in the news that will be analyzed by researchers. This study aims to find out how SARA is represented in the statement of the Head of BPIP in the news Detik.com.The results of this study in terms of text analysis have been narrated through repetition, themes, modalities, and diction referred to in the head of BPIP Call Religion to Be the Greatest Enemy of Pancasila at detik.com. In terms of Discourse Practice by looking at the level of text production and text consumption in the head of BPIP's call Religion Becomes the Greatest Enemy of Pancasila. In terms of Sociocultural Practice the Head of BPIP made a statement related to the SARA because he had just held the position of Head of BPIP and added that detik com had a close relationship with Yudian Wahyudi in line with the power of the CT Corp owner's son making the detik.com media faster to carry out the process text production. The statement made by Yudian Wahyudi in the news on detik.com which mentions that the biggest enemy of Pancasila today is that Religion arises because of the social events that occurred and were experienced by Indonesian people in the past so that Yudian Wahyudi easily made such statements.